Pengaruh Variasi Kuat Arus Listrik dan Waktu Electroplating Nickel-Chrome terhadap Ketebalan Lapisan pada Permukaan Baja Karbon Rendah - Heribertus Sukarjo; R. Soelarso Pani (Jurnal Engine: Energi, Manufaktur, dan Material, 2018)
The development and progress of science and technology in the metal plating industry has become a field of work that is experiencing rapid advances ranging from the type of coating, a coating material that is used, and the results of a layer. The metal plating industry needs not only demand resistance to corrosion, but also the strength of the material, has a beautiful appearance, and has a high economic value. one of them, namely by means of electroplating coating. The purpose of this research is to know the influence of variations in the strength of an electric current and time of electroplating nickel-chrome against the thickness of the surface layer of low carbon steel. The benefits of this research are expected to add to the knowledge about the coating on the process of electroplating nickel-chrome and can apply it. In the activities of this research material used is low carbon steel plates with a size 40 mm x 25 mm x 1 mm with the number 27 specimens are coated using electroplating method with the variation of strength of electric current of 0.5 A, 1 A, 1.5 A and time electroplating 10 minutes, 15 minutes, 20 minutes. Testing done next the thickness of the layer. Results of the study showed that the highest hardness of nickel-chrome electroplating process occurs on a variation of value the highest layer thickness variation in the strength of the current 1.5 A long coating 20 minutes 1.97 µm.